Thermal and mechanical properties of injection moulded heat-treated oil palm empty fruit bunch fibre-reinforced high-density polyethylene composites - Nordin, Nur Afifah; Abd Rahman, Nor Mas Mira; Hassan, Aziz (Taylor & Francis, 2019)
Oil palm empty fruit bunch (OPEFB) was heat treated at 180°C using a vacuum oven for one hour, extruded and compounded with high-density polyethylene at 10%, 20% and 30% weight fraction. The composites then were injection moulded into dumb-bell shaped specimens. The effect of composition and heat treatment on the thermal properties of composites were investigated using Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The tensile and flexural properties were also tested using an Instron Universal Testing Machine. TGA shows an increase in the degradation peak temperature of the heat-treated composites. DSC revealed an increasing trend in the degree of crystallinity (Xc) of the matrix as the heat-treated empty fruit bunch was used as a filler. An increment in the tensile modulus and tensile strain were observed for the treated fibre composites. In addition, the tensile strength value was increased for treated fibre composites with lower fibre loading. © 2019, © 2019 Institute of Materials, Minerals and Mining Published by Taylor & Francis on behalf of the Institute.